Degradation of triclosan in aqueous solution by dielectric barrier discharge plasma combined with activated carbon fibers. (February 2016) - Xin, Lu; Sun, Yabing; Feng, Jingwei; Wang, Jian; He, Dong
Abstract: The degradation of triclosan (TCS) in aqueous solution by dielectric barrier discharge (DBD) plasma with activated carbon fibers (ACFs) was investigated. In this study, ACFs and DBD plasma coexisted in a planar DBD plasma reactor, which could synchronously achieve degradation of TCS, modification and in situ regeneration of ACFs, enhancing the effect of recycling of ACFs. The properties of ACFs before and after modification by DBD plasma were characterized by BET and XPS. Various processing parameters affecting the synergetic degradation of TCS were also investigated. The results exhibited excellent synergetic effects in DBD plasma-ACFs system on TCS degradation. The degradation efficiency of 120 mL TCS with initial concentration of 10 mg L −1 could reach 93% with 1 mm thick ACFs in 18 min at input power of 80 W, compared with 85% by single DBD plasma. Meanwhile, the removal rate of total organic carbon increased from 12% at pH 6.26–24% at pH 3.50. ACFs could ameliorate the degradation efficiency for planar DBD plasma when treating TCS solution at high flow rates or at low initial concentrations. A possible degradation pathway of TCS was investigated according to the detected intermediates, which were identified by liquid chromatography-hybrid quadrupole time-of-flight mass spectrometry (LC–QTOF-MS) combined with theoretical calculation of Gaussian 09 program. Highlights: Degradation of aqueous triclosan by using DBD plasma and ACFs was investigated. The ACFs showed efficient synergistic effect with DBD plasma for various processing parameters. The ACFs achieved modification and in situ regeneration during triclosan degradation. Main intermediates and the pathway of triclosan degradation by DBD plasma were proposed.